An Analysis of Transformational Processes in the Spiritual Life and Traditions of Central Asian Jews - Isroil Haydarov (Genius Journals, 2022)
This article analyzes the spiritual and ceremonial life of the Jews who entered the Central Asian region in the early Middle Ages on the basis of ethnographic materials.
Keywords: Jews; Central Asia; spiritual culture; rituals